2012
DOI: 10.2340/16501977-1003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rehabilitation programmes for patients on long-term sick leave for burnout: A 3-year follow-up of the REST study

Abstract: A multimodal rehabilitation including cognitively oriented behavioural rehabilitation and Qigong showed positive effects 3 years after the end of intervention. The results indicate that, for many burnout patients on sick-leave, it takes time to implement cognitive tools and to establish new behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 24 publications
4
39
1
2
Order By: Relevance
“…The findings from the two other Swedish studies with long-term follow-ups showed improvements in RTW rates, though not as function of intervention [5, 15]. It should be kept in mind that Grossi’s and Santell’s [5] study was very small (n = 12 per group), which limits the ability to detect such differences.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The findings from the two other Swedish studies with long-term follow-ups showed improvements in RTW rates, though not as function of intervention [5, 15]. It should be kept in mind that Grossi’s and Santell’s [5] study was very small (n = 12 per group), which limits the ability to detect such differences.…”
Section: Discussionmentioning
confidence: 91%
“…It should be kept in mind that Grossi’s and Santell’s [5] study was very small (n = 12 per group), which limits the ability to detect such differences. Stenlund’s [15] study had a response rate of 65% compared to their 1-year follow-up, which due to possible systematic differences between drop-outs and participants may introduce some uncertainty as regards interpreting the results, as discussed by the authors. Van Oostrom et al [9] conducted a randomized control trial study of an intervention model that seems to share some characteristics with our model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A follow up period of one year may be too short to evaluate the long term effect of the rehabilitative intervention, especially in case of relative stabile strait like alexithymia. More time would be needed to implement cognitive tools and to establish new behaviors [54]. The EERIP took 6 months and included 31 active days.…”
Section: Limitationsmentioning
confidence: 99%
“…Subsequent evaluation tools were adapted for general use, leading to the Malach-Pines Burnout Measure Scale, short version (BMS-10), 10 in which the number of items was reduced from 22 down to 10. There is no standard treatment for burnout. Different forms of psychological intervention are usually attempted; 11,12 with verbal exchange playing an important role. Medical treatment for burnout largely centres on the administration of anxiolytic and/ or antidepressant agents, which are not necessarily effective.…”
Section: Introductionmentioning
confidence: 99%